2022
DOI: 10.1158/1541-7786.mcr-21-0657
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Profiling Shows BAP1 Loss Is Associated with Upregulated Cell Adhesion Molecules in Uveal Melanoma

Abstract: BRCA1-associated protein 1 (BAP1) is a tumor suppressor gene that is mutated in cancer, including uveal melanoma (UM). Loss-of-function BAP1 mutations are associated with UM metastasis and poor prognosis, but the mechanisms underlying these effects remain unclear. Upregulation of cell-cell adhesion proteins is involved with collective migration and metastatic seeding of cancer cells. Here, we show that BAP1 loss in UM patient samples is associated with upregulated gene expression of multiple cell adhesion mole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Another explanation is that SDC2 may have complex interactions with other genes and the function of SDC2 may be realized by participation of other genes. Interestingly, a recent study showed that BAP1 loss is associated with upregulated expression of SDC2 in UVM, while knockdown of SDC2 did not have any functional inhibition [47]. Considering that single knockdown of SDC2 has not overt effect, further studies are needed to determine the exact role of SDC2 in UVM.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that SDC2 may have complex interactions with other genes and the function of SDC2 may be realized by participation of other genes. Interestingly, a recent study showed that BAP1 loss is associated with upregulated expression of SDC2 in UVM, while knockdown of SDC2 did not have any functional inhibition [47]. Considering that single knockdown of SDC2 has not overt effect, further studies are needed to determine the exact role of SDC2 in UVM.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function BAP1 mutations are associated with higher tumor grade and poorer prognosis in ccRCC [ 26 ]. Previous research in uveal melanoma demonstrated that BAP1 could regulate the expression of multiple cell adhesion molecules [ 27 ]. As one adhesion molecule, BCAM may also be regulated by BAP1 in ccRCC, although there is no evidence yet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper [49] proposed that the cell adhesion molecules CADM1, SDC2 and CDH1 are up-regulated in BAP1 mutant human UM. While these three genes were also up-regulated in our analysis of human UM, Cadm1 and Sdc2 were not DE in the mouse dataset and Cdh1 (Ecadherin) was down-regulated, which is more consistent with an up-regulation of EMT, the general overall pattern that we observed.…”
Section: Shared Transcriptional Changes In Bap1 Mutant Um Identify Em...mentioning
confidence: 99%